Discriminating fingerprints of chronic neuropathic pain following spinal cord injury using artificial neural networks and mass spectrometry analysis of female mice serum - Deulofeu, Meritxell; Peña-Méndez, Eladia M; Vaňhara, Petr; Havel, Josef; Moráň, Lukáš; Pečinka, Lukáš; Bagó-Mas, Anna; Verdú, Enrique; Salvadó, Victoria; Boadas-Vaello, Pere (Neurochemistry international, 2024)
Spinal cord injury (SCI) often leads to central neuropathic pain, a condition associated with significant morbidity and is challenging in terms of the clinical management. Despite extensive efforts, identifying effective biomarkers for neuropathic pain remains elusive. Here we propose a novel approach combining matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) with artificial neural networks (ANNs) to discriminate between mass spectral profiles associated with chronic neuropathic pain induced by SCI in female mice. Functional evaluations revealed persistent chronic neuropathic pain following mild SCI as well as minor locomotor disruptions, confirming the value of collecting serum samples. Mass spectra analysis revealed distinct profiles between chronic SCI and sham controls. On applying ANNs, 100% success was achieved in distinguishing between the two groups through the intensities of m/z peaks. Additionally, the ANNs also successfully discriminated between chronic and acute SCI phases. When reflexive pain response data was integrated with mass spectra, there was no improvement in the classification. These findings offer insights into neuropathic pain pathophysiology and underscore the potential of MALDI-TOF MS coupled with ANNs as a diagnostic tool for chronic neuropathic pain, potentially guiding attempts to discover biomarkers and develop treatments.
Keywords: Chronic Pain; poranění míchy; neuronové sítě; Female; Spinal Cord Injuries; Neural Networks, Computer; Biomarkers; zvířata; myši; myši inbrední C57BL; chronická bolest; Mice; neuralgie; Neuralgia; ženské pohlaví; biologické markery; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Mice, Inbred C57BL; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization